Maximum Ride, The Manga - Book 3 3 - Lee, NaRae; Patterson, James 1947-; Blackman, Abigail (New York : Yen Press/Hachette Book Group, 2010)
"Narrowly surviving their encounter with Erasers in New York City, the flock is following up a lead on their pasts in Washington, D.C. But what they find waiting for them is-- a home? How will the flock adjust to a real school-- one that doesn't involve mad scientists and genetic freaks?"--P. [4] of cover.
Keywords: Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc; Adventure stories -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Genetic engineering -- Fiction; Adventure and adventurers -- Fiction; Teenagers -- Fiction; Cartoons and comics; New York (N.Y.) -- Comic books, strips, etc; Washington (D.C.) -- Comic books, strips, etc; New York (N.Y.) -- Fiction; Washington (D.C.) -- Fiction; Science fiction comic books, strips, etc; Graphic novels